Peran Pemerintah dalam Mengatasi Human Trafficking di Kepulauan Riau - Dewi, Ayu Efrita; Rahman, Abdu; Nasution, Muhammad Farhan (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2023)
Human trafficking is an issue that receives widespread attention in Indonesia and the world. There have been cases of human trafficking in the Riau Islands, for example, when Indonesian migrant workers (TKI) seeking employment abroad (in Malaysia) are promised jobs as domestic helpers with high wages, but in reality, they are exploited as commercial sex workers. Therefore, Indonesia needs to address this problem in order to reduce the number of victims and strengthen the laws and regulations for migrant workers. The Indonesian government has made internal (local and national) and external efforts to combat human trafficking in the Riau Islands. However, there are still challenges in implementing these policies, resulting in ineffective coordination among responsible institutions. This indicates the ineffectiveness of government policies in addressing and preventing human trafficking. To address the complexity of human trafficking, comprehensive policies are needed that do not conflict with each other among institutions. Additionally, bilateral or multilateral cooperation is important to overcome differences in interests and approaches to tackling human trafficking issues. The role of local governments is also crucial in addressing human trafficking, such as the establishment of Trauma Center Shelter (RPTC) in Tanjungpinang City, in accordance with the Provincial Regulation of the Riau Islands Number 12 of 2007 on the Elimination of Trafficking in Women and Children. RPTC actively engages in the psychosocial rehabilitation of human trafficking victims, involving social workers in the process. Through psychosocial rehabilitation services provided at RPTC, it is hoped that human trafficking victims can recover from trauma and reintegrate socially in the community.